PENGARUH TINGKAT KEDISIPLINAN APARAT DESA TERHADAP KUALITAS PELAYANAN PADA MASYARAKAT DI KECAMATAN PEDAN KABUPATEN KLATEN TAHUN 2012 - Mulyani, Mei; Suryono, Hassan; Permata, Rima Vien (Educitizen, 2017)
This research  about  influence of the discipline of village officials to the quality of public services in the District Pedan Klaten 2012. The study population is the entire apparatus of villages in the district Pedan totaling 214 people. The sampling technique used is stratified random sampling disproporcionate, obtained total sample of 135 people. Data collection techniques by using a questionnaire. Test conditions used are normality test, independent, and a linearity test. Phase calculations used in the data analysis is influence the calculation of the amount of the contribution, and the last is the calculation of a simple regression analysis. The conclusions of this study is that there is the influence of the level of discipline village officials on the quality of public services in the District Pedan Klaten 2012. It can be seen from the regression equation obtained is = 24.448 + 0.522 X. The contribution of the effect of variable X on Y is equal to 29.24%. Kata Kunci : Disiplin, Aparat Desa, Kualitas Pelayanan